The archaeology of Swartkrans cave, Gauteng, South Africa: new excavations of members 1 and 4 - Sutton, Morris. B (My University, 2013)
Swartkrans Cave, famous for abundant hominin fossils of P. robustus and the site where the first evidence of the co-existence of two hominin species was recovered, has yielded a wealth of information on early hominin behaviour. In 2005 a new program of research and excavation began at the site, and its results form the central part of this thesis. This study has focused on the early Pleistocene Member 1 deposits which include an Earlier Stone Age industry and the late Pleistocene Member 4 Middle Stone Age deposits. The thesis has four areas of focus. First the new work has resulted in clarification and new interpretations for the formation of the hominin rich Hanging Remnant deposit of Member 1, which lacks stone tools. This extensive calcified conglomerate which spans most of the north wall of the cave is now seen as a non-homogenous unit that represents material entering from at least four avens. However, this study also established that the newly exposed central portion of the Hanging Remnant and the hominin fossil-rich northwest corner infill worked by Robert Broom in the 1940s derived from the same depositional episode. Secondly, the new excavations in the Lower Bank of Member 1 have resulted in an enlargement of the previously ambiguous Earlier Stone Age assemblage. Analysis of this new assemblage, in conjunction with recently released dating results, has now confirmed that the artefacts belong to the Oldowan Industrial Complex. Thirdly, new excavations in the Member 4 deposit have resulted in the recovery of over 3,200 Middle Stone Age (MSA) stone tools and a clearer understanding of their context. The stone tool-bearing deposits of Member 4 are now understood to derive from a surface colluvium, rather than a cave infill. This MSA assemblage consists of a high number of retouched pieces that are dominated by steep-sided scrapers and denticulated scrapers with a near-absence of points. The technology of a variety of core types suggests a superior understanding of raw material flaking qualities by the tool makers. The limited types of formal tools suggest that the site was used for one or more specific activities, rather than for a range of activities by the tool makers. Fourthly, excavation of the deposits underlying the Member 4 colluvium has resulted in the discovery of two previously unknown hominin-bearing deposits. It is now established that what was originally called Member 4 is composed of three distinct deposits. The lowest of these is an east extension of the Member 1 Lower Bank (LB East Extension), which has yielded P. robustus fossils. This is overlain by a large talus cone (TCD), which also has yielded P. robustus fossils. The latter is capped by flowstone dated to ~110,000 years, followed by the MSA-tool bearing colluvium.
Keywords: Prehistoric peoples - South Africa - Swartkrans Cave.; Cave dwellers.; Caves - South Africa - Swartkrans Cave.; Human beings - Origin.; Fossil hominids - South Africa - Swartkrans Cave.; Anthropology, Prehistoric.; Swartkrans Cave (South Africa)